Strategi Reboisasi untuk Mitigasi Perubahan Iklim dan Pemulihan Ekosistem di Desa Pamarican - Putri Anggraeni Salsabila; Ranti Lestari; Savanna Maura Priasta; ST Noor Alliqa Zahara; Lina Karlina (Jurnal Kemitraan Masyarakat, 2024)
This community service was carried out with the aim of reducing the risk of landslides by planting 100 albasia tree seedlings in areas prone to landslides. This activity involved the entire community of Pamarican Village, along with Galuh University KKN students. Through the preparation stage, socialization, training, and active participation of the community, this reforestation activity succeeded in having a positive impact. In addition to potentially reducing the risk of landslides, tree planting also provides ecological and economic benefits, such as water management, improved air quality, and potential income from sustainable forest products. With collective awareness and community involvement, it is hoped that steps to anticipate flood disasters can be more effectively carried out, maintain a healthy environment, and create sustainable environmental sustainability in Pamarican District, Ciamis Regency.